Dominating the Space: Uncover the Existence of Street Vendors in Public Space, The case of Tengku Amir Hamzah Square, Stabat, Indonesia - Bambang Karsono; Mohammad Shihadeh A. Arar; Irsanuddin Luthfi; Deni Deni (International Journal of Engineering, Science and Information Technology, 2022)
The existence of street vendors tends to dominate public spaces, which is physically considered to affect the physical quality. Tengku Amir Hamzah Square (TAHS) in Stabat is a famous local public space. Its strategic location triggers the growth of street vendors who provide attractions for visitors. Initially, TAHS was designed not to provide a space for street vendors, and the local regulation said that the presence of street vendors was prohibited. The existence of street vendors in TAHS who occupy this public space has emerged with pros and cons. This phenomenon became the reason for this study to be conducted, specifically to uncover the pattern of temporary space and space-forming elements created by street vendors and their relationship with the public's interest in visiting TAHS. The mixed-method research approach is used in this study to disclose and analyze data descriptively. Mapping and observation were carried out to obtain quantitative data, including layout, the number of street vendors, merchandise types, and distribution patternshod of displaying. The elements that form public spaces implemented by street vendors are obtained through observations and photo-trekking, and 58 respondents were involved in the interviews. Findings indicate that the strategic location and fluent permeability to and from TAHS have made this potential street vendor attraction popular among the locals. The activity created in this area acts as a generator of movement, especially at night, attracting people to come and walk through the existing street vendor outlets, contributing to urban livability.